Kidneys From α1, 3-Galactosyltransferase Knockout/Human Heme Oxygenase-1/Human A20 Transgenic Pigs Are Protected From Rejection During Ex Vivo Perfusion With Human Blood. Issue 6 (July 2015) - Ahrens, Hellen E.; Petersen, Björn; Ramackers, Wolf; Petkov, Stoyan; Herrmann, Doris; Hauschild-Quintern, Janet; Lucas-Hahn, Andrea; Hassel, Petra; Ziegler, Maren; Baars, Wiebke; Bergmann, Sabine; Schwinzer, Reinhard; et al.
Abstract : Background: Multiple modifications of the porcine genome are required to prevent rejection after pig-to-primate xenotransplantation. Here, we produced pigs with a knockout of the α1, 3-galactosyltransferase gene ( GGTA1 -KO) combined with transgenic expression of the human anti-apoptotic/anti-inflammatory molecules heme oxygenase-1 and A20, and investigated their xenoprotective properties. Methods: The GGTA1 -KO/human heme oxygenase-1 (hHO-1)/human A20 (hA20) transgenic pigs were produced in a stepwise approach using zinc finger nuclease vectors targeting the GGTA1 gene and a Sleeping Beauty vector coding for hA20. Two piglets were analyzed by quantitative reverse-transcription polymerase chain reaction, flow cytometry, and sequencing. The biological function of the genetic modifications was tested in a 51 Chromium release assay and by ex vivo kidney perfusions with human blood. Results: Disruption of the GGTA1 gene by deletion of few basepairs was demonstrated in GGTA1 -KO/hHO-1/hA20 transgenic pigs. The hHO-1 and hA20 mRNA expression was confirmed by quantitative reverse-transcription polymerase chain reaction. Ex vivo perfusion of 2 transgenic kidneys was feasible for the maximum experimental time of 240 minutes without symptoms of rejection. Conclusions: Results indicate that GGTA1 -KO/hHO-1/hA20 transgenic pigs are a promising model to alleviate rejection and ischemia-reperfusion damage in porcine xenografts and could serve as a background for further genetic modifications toward the production of a donor pig that is clinically relevant for xenotransplantation. Abstract : Supplemental digital content is available in the text.